4.2x=3.6x+13

Simple and best practice solution for 4.2x=3.6x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4.2x=3.6x+13 equation:



4.2x=3.6x+13
We move all terms to the left:
4.2x-(3.6x+13)=0
We get rid of parentheses
4.2x-3.6x-13=0
We add all the numbers together, and all the variables
0.6x-13=0
We move all terms containing x to the left, all other terms to the right
0.6x=13
x=13/0.6
x=21+0.4/0.6

See similar equations:

| I4x-3I=7 | | 5(4w+8)=2 | | 16+9=x^2 | | 2x=3•86 | | 2x-20°=5x-50° | | F(x)=6-2x-3 | | 2x=3•96 | | 32=8(m+36) | | 13+7u=-15 | | 6c-25=35 | | 64=8(y-80) | | -10x+8x+5,8=-2x+3 | | 5(2n–6)=20 | | 1325x65=65x | | (Q-8)x4=32 | | 2/3x−2=22 | | 5/6×m=35.1 | | -8m=-4.0 | | x-4.5=9.7-3.2 | | x²x=5 | | 0.5x-1.4=16.7 | | 3(i-8)=9 | | y^2=1-12y | | 3.14n+2=12.99 | | 85+w=120 | | 47=26-j | | 19-x(38)=0 | | -4-4x+1+x=1-4x | | 16-4n=-6n+6-2 | | -12-3b=b+4 | | 16-5m=5-6m+3 | | -13=-4+r |

Equations solver categories